2003
DOI: 10.1017/s0021859603002983
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of observer performance in a subjective scoring system: visual classification of the gait of cows

Abstract: SU MMARYAs with any measurement procedure, the performance of a subjective classification procedure must be evaluated. Observers have to be trained and their performance has to be assessed, preferably on a regular basis, to guarantee sufficient consistency and accuracy of classification results. The current paper is a study of observer performance where observers were asked to classify the gait of cows from video recordings. Gait was classified in nine ordered categories (ranging from 1=normal gait to 9=severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…In order to reduce memory effects, we manipulated one of the repeats (Engel et al, 2003) by mirroring the videos horizontally. However, to verify the potential effect of mirroring on intra-OR, we also presented each video for a third time, again in its original format.…”
Section: Ethics Statementmentioning
confidence: 99%
“…In order to reduce memory effects, we manipulated one of the repeats (Engel et al, 2003) by mirroring the videos horizontally. However, to verify the potential effect of mirroring on intra-OR, we also presented each video for a third time, again in its original format.…”
Section: Ethics Statementmentioning
confidence: 99%
“…The degree of lameness is described using a validated clinical gait-scoring system (Sprecher et al, 1997;Flower and Weary, 2006), this being a subjective method for assessing lameness. However, locomotion scoring requires observer training and may not be sensitive enough to detect slight gait alterations (Engel et al, 2003;Tadich et al, 2010). The difficulties in evaluating the stride and postural characteristics as well as the reproducibility of scoring mildly lame cows are most challenging (Engel et al, 2003;Holzhauer et al, 2005;Flower and Weary, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, locomotion scoring requires observer training and may not be sensitive enough to detect slight gait alterations (Engel et al, 2003;Tadich et al, 2010). The difficulties in evaluating the stride and postural characteristics as well as the reproducibility of scoring mildly lame cows are most challenging (Engel et al, 2003;Holzhauer et al, 2005;Flower and Weary, 2006). In addition, cows showing impaired locomotion may not always express all traits described by a certain locomotion-scoring method (Schlageter-Tello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The left-right differences of the stance-and swing-phase durations tended to decrease after claw trimming when cows walked on asphalt floor. Many studies reported that foot pathologies at certain stages (slight to moderate degree) do not affect the gait score of cows (Engel et al, 2003;Tadich et al, 2010). Furthermore, we excluded lame cows from the analysis, as a previous study showed that lame cows have different walking patterns on different floor types (Flower et al, 2007).…”
Section: Discussionmentioning
confidence: 99%